Estudos de bioequivalência de brometo de n-butilescopolamina em forma de comprimidos e de seus metabólicos em plasma humano de voluntarios sadios - Suenaga, Eunice Mayumi [UNIFESP] (2016)
The N-butylscopolamine bromide though a drug widely widespread and used as an antispasmodic, both in the population as in Worldwide, there are very few scientific papers published about him, especially in relation to its pharmacokinetics: absorption, metabolism and excretion. With the advance of techniques of separation and quantitation of chemical substances present in biological fluids and tissues, as well as the development of equipment with high sensitivity, capable of detecting traces, today we trace farrnacocinético profile of parent drug and metabolites, even those drugs considered action site with low absorption such as N-butyl scopolamine. In this work we developed three methods of extraction and detection by LCMS / MS capable of identifying N-butylscopolamine in human plasma after ingestion a single 10mg tablet of Buscopan, the first two with purpose of quantifying the N-butylscopolamine to determine Bioequivalence between formulations Furp (Test) and Buscopan (Reference) and third to identify potential metabolites of N-butyl scopolamine .in plasma human .. The first two methodologies were developed and validated and considered suitable for quantification of N-butylscopolamine in human plasma, the first by online solid-liquid extraction (online SPE) and high performance liquid chromatography efficiency coupled with mass spectrometry (LC-MSIMS) with a range of concentration:. 0.05 to 40 ng / ml, range withdrawn from the literature. The second methodology Liquid-liquid extraction and chromatography coupled with ultra efficiency mass espectrôrnetro (FPLC-LLE-MS / MS), with a concentration range of 1 to 1000 pg / ml, which allowed quantify and trace the pharmacokinetic profile of Nbutilescopolamina for the determination of bioequivalence between the two formulations butylscopolamine bromide, following ingestion of a single 10 mg tablet. Using 58 volunteers, due to high intra-individual variability, proven by statistical calculations (38%), the two formulations: tablet Coated 10mg butylscopolamine bromide FURP Buscopan and '' were 25